2014
DOI: 10.1186/1471-2350-15-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between interleukin-1 gene polymorphisms and sepsis risk: a meta-analysis

Abstract: BackgroundPrevious epidemiological studies have presented conflicting evidence regarding associations between interleukin-1 (IL-1) polymorphisms and sepsis susceptibility. We have performed a meta-analysis to evaluate possible associations between IL-1 polymorphisms and sepsis risk.MethodsEligible literature was retrieved from PubMed, Embase and Web of Knowledge databases until Jun 15, 2013. The pooled odds ratio (OR) and 95% confidence interval (CI) were calculated using random-effects model in the overall an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 43 publications
0
22
0
8
Order By: Relevance
“…This process is critical in the pathogenesis of sepsis and septic shock. Moreover, sepsis susceptibility or resistance has been related to genetic variations within this gene . In our study, the presence of the minor rs16944 A allele in homozygosis was related to the onset of septic shock and death (septic shock‐related death).…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This process is critical in the pathogenesis of sepsis and septic shock. Moreover, sepsis susceptibility or resistance has been related to genetic variations within this gene . In our study, the presence of the minor rs16944 A allele in homozygosis was related to the onset of septic shock and death (septic shock‐related death).…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, AA genotype has showed a reduced Aspergillusinduced IL-1b production and TNF a secretion by PBMCs [21]. However, there are some discrepancies as some studies did not find any genetic association of rs16944 with IL-1b levels [20], infection or sepsis [3,23,27,37]. In non-European population, the rs16944 AA genotype has been related to lower risk of infection [19], and the GG genotype was associated with production of IL-1b [38] and higher risk of infection [24,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invitro studies have shown that allele A in the promoter (upstream of the transcriptional start site) SNP 2511 G>A is related to increased lipopolysaccharide (LPS)induced IL-1B protein secretion [36]. In a recent metaanalysis, the SNP 2511A allele was less frequent in patients with sepsis compared to controls among Caucasians (one study) and Asians (four studies), although the results failed to reach statistical significance [37]. The same direction of the effect was observed in our study for the same genetic model.…”
Section: Discussionmentioning
confidence: 99%
“…Besides silicosis, this polymorphism has been previously associated with the modulation of the severity of other inflammatory diseases, such as Hashimoto's thyroiditis, Graves’ disease, periodontitis, and rheumatoid arthritis . Second, the −889C/T (rs1800587) SNP is located in the 5′‐untranslated region (5′‐UTR) of the IL1A gene and plays an important role in the transcriptional regulation of the gene, leading to an increased serum protein level . This polymorphism was previously associated with periodontitis, sepsis, and allergic rhinitis .…”
Section: Introductionmentioning
confidence: 99%